“El Triunfo” Photovoltaic Power Plant; Rural Development Study - José Emilio Camejo Cuán; Rubén Ramos Heredia; Roger Proenza Yero (Journal La Sociale, 2021)
The results of rural electrification in Cuba, from Photovoltaic Solar Energy, are presented as part of the technical-economic feasibility study of the use of medium-power Photovoltaic Plants in tropical climate conditions, based on the experiences obtained for more than 20 years of operation of the photovoltaic plant in the rural community "Santa María del Loreto" and its generalization in the photovoltaic plant in the rural community "El Triunfo". Both facilities located in the mountainous area of the Songo - La Maya Municipality, Santiago de Cuba Province. The photovoltaic plant benefits the inhabitants of the rural community "El Triunfo", guaranteeing a high-quality, uninterrupted and stable electrical service, as well as a considerable change in the profiles of use of free night time with an increase in the activities of Entertainment, information with high-quality access to the mass media such as television and radio, all of this has influenced local community development, with special emphasis on the humanization of the work of women and housewives.